TISSUE ENGINEERING AND REGENERATIVE MEDICINE TECHNOLOGIES IN THE TREATMENT OF ARTICULAR CARTILAGE DEFECTS - Yu. B. Basok; V. I. Sevastianov (Вестник трансплантологии и искусственных органов, 2017)
Some of the most pressing health problems of the industrial society are the damage and degeneration of articular cartilage associated with the limited capacity of tissues to regenerate. The review describes the existing and developing technologies for the recovery and replacement of damaged joint cartilage tissue. The results obtained are analyzed covering two major areas: the stimulation of regeneration of damaged cartilage tissue and the growing of cartilage tissue elements in bioreactors.